Kala Azar- A Diagnostic Dilemma - A Case Report - Adhikari, P; Pandey, P R; Sharma, A; Basnet, S; Singh, SK; Pande, J S (Medical Journal of Shree Birendra Hospital, 2006)
Kala Azar- A Diagnostic Dilemma - A Case Report